A meteor head echo analysis algorithm for the lower VHF band - Kero, J.; Szasz, C.; Nakamura, T.; Terasawa, T.; Miyamoto, H.; Nishimura, K. (Annales geophysicae (1988), 2012)
We have developed an automated analysis scheme for meteor head echo observations by the 46.5 MHz Middle and Upper atmosphere (MU) radar near Shigaraki, Japan (34.85° N, 136.10° E). The analysis procedure computes meteoroid range, velocity and deceleration as functions of time with unprecedented accuracy and precision. This is crucial for estimations of meteoroid mass and orbital parameters as well as investigations of the meteoroid-atmosphere interaction processes. In this paper we present this analysis procedure in detail. The algorithms use a combination of single-pulse-Doppler, time-of-flight and pulse-to-pulse phase correlation measurements to determine the radial velocity to within a few tens of metres per second with 3.12 ms time resolution. Equivalently, the precision improvement is at least a factor of 20 compared to previous single-pulse measurements. Such a precision reveals that the deceleration increases significantly during the intense part of a meteoroid's ablation process in the atmosphere. From each received pulse, the target range is determined to within a few tens of meters, or the order of a few hundredths of the 900 m long range gates. This is achieved by transmitting a 13-bit Barker code oversampled by a factor of two at reception and using a novel range interpolation technique. The meteoroid velocity vector is determined from the estimated radial velocity by carefully taking the location of the meteor target and the angle from its trajectory to the radar beam into account. The latter is determined from target range and bore axis offset. We have identified and solved the signal processing issue giving rise to the peculiar signature in signal to noise ratio plots reported by Galindo et al. (2011), and show how to use the range interpolation technique to differentiate the effect of signal processing from physical processes.